2018
DOI: 10.1177/8755122518794023
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Knowledge of Veterinary Pharmacotherapy and the Impact of an Educational Intervention

Abstract: Background: To date, there is very limited data regarding pharmacists' preparedness to handle animal prescriptions. No previous studies exist examining the impact of a veterinary-pharmacy-focused educational intervention. Objective: To assess pharmacists' baseline knowledge of veterinary pharmacotherapy, as relevant to their professional responsibilities, and assess the impact of a piloted educational program. Methods: Two studies were conducted. The first study involved a statewide assessment of pharmacists' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Similarly, in Grenada, a study among poultry farmers and employees found a low awareness of AMR [ 75 ], and in Tanzania, there was generally low public awareness of ABU and AMR [ 76 ]. This low awareness of poultry ABU and AMR may suggest the need for enhanced educational programs among all stakeholders [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Grenada, a study among poultry farmers and employees found a low awareness of AMR [ 75 ], and in Tanzania, there was generally low public awareness of ABU and AMR [ 76 ]. This low awareness of poultry ABU and AMR may suggest the need for enhanced educational programs among all stakeholders [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 For practicing pharmacists, veterinary pharmacy training is generally limited and may not be prioritized; nine out of ten pharmacists reported no previous training in veterinary pharmacy. 8 Lack of adequate training is a common issue in both the USA and abroad, and insufficient educational experiences could hinder pharmacists from safely dispensing veterinary medications or appropriately counseling clients. 9 , 10 Additionally, community pharmacists may be unaware of roles in which they are legally prohibited from engaging.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists have not only reported inadequate knowledge of veterinary pharmacotherapy but also of legal aspects pertinent to compounding for veterinary patients. 8 For example, pharmacists may be unaware they cannot legally recommend over-the-counter (OTC) medications for veterinary patients without the recommendation or a prescription from a veterinarian. Without a clear understanding of their roles, community pharmacists may endanger pet health and place themselves in legal jeopardy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Justin-Temu et al found that 79% of pharmacists reported substantial satisfaction/progress in their veterinary knowledge after having training in veterinary pharmacy [ 12 ]. Besides, Young et al underscored the same growing knowledge of veterinary pharmacotherapy of the retail pharmacists, based on a pretest and posttest after having an educational program [ 26 ]. Our study revealed that two-thirds of pharmacists did not have courses in veterinary pharmacy during their undergraduate studies.…”
Section: Discussionmentioning
confidence: 99%